Effect of temperature on crystallite sizes of copper sulfide nanocrystals prepared from copper(II) dithiocarbamate single source precursor. (1st March 2016) - Botha, Nandipha L.; Ajibade, Peter A.
Abstract: We report the synthesis of CuS nanoparticles using [Cu(butdtc)2 ] as single source precursor thermolysed at two different temperatures. The products were characterized by UV–vis absorption spectroscopy, X-ray diffraction, Transmission electron microscopy, scanning electron microscopy, energy dispersive X-ray analysis and atomic force microscopy. The absorption spectra of the CuS nanocrystals are blue shifted and the XRD were indexed to the hexagonal phase of CuS with nanoparticles obtained at 120 °C showing well defined crystalline structure compared to those obtained at 180 °C. Transmission electron microscopy images showed particles that are almost spherical in shapes with average crystallite sizes of 21–38 nm for CuS1 prepared at 180 °C and 3–7 nm for CuS2 prepared at 120 °C and confirms that the chosen reaction temperature determine the crystallite sizes of the nanoparticles.